Cheese whey exploitation in Brazil: a questionnaire survey - TRINDADE,Monika B. (2019)
Abstract This study aimed to carry out a diagnosis of the cheese whey exploitation by the Brazilian dairy industry using a questionnaire survey. The dairy industries (n=100) were mainly from Southeast (55%) and South (25%) regions and supervised by the Federal Inspection System (80%). Most of them produced (67%) and processed (60%) sweet cheese whey, using it in whey dairy beverages (60%), Ricotta (20%), whey concentrate (15%), and milk blends (5%), which were resold for supermarkets (53%) or industries (20%). However, 27% of the industries discard whey in the effluent treatment system or use as animal feed, suggesting a market for using this by-product.